Paternal Response to Ultrasound Predicts Increased Paternal-Fetal Attachment. (December 2021) - Tolman, Richard M.; Walsh, Tova; Bybee, Deborah; Davis, Neal; Reed, Lauren A.; Safyer, Paige; Singh, Vijay
Utilizing data from a longitudinal online survey of couples expecting their first child, this study sought to examine the trajectory of paternal-fetal attachment across the three trimesters of pregnancy. Expectant fathers (N=124) who completed at least the first two assessments were included in the analysis. Attachment was assessed using the Paternal Antenatal Attachment Scale, and paternal response to the ultrasound was measured with a four-item scale developed for this study. Longitudinal multilevel regression was used to model change in paternal-fetal attachment across assessments. Paternal-fetal attachment increased among all fathers, including those who showed less response to ultrasound and those who reported the pregnancy as mistimed or undesired. However desired pregnancy and stronger paternal response to ultrasound were associated with a larger increase in paternal-fetal attachment. The findings of the study have implications for the support of paternal-fetal attachment in health care and other settings.